Dental Foreign Body in the Right Bronchi of Elderly Patients: A Case Report - Mc. Syaiful Ghazi Yamani; Salim Said Thalib; Suryani Padua Fatrullah; Indana Eva Ajmala; Gemilang Khusnurrokhman (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: The aspiration of foreign bodies into the airway is rare in adults, except in the elderly with impaired consciousness or difficulty swallowing. Serious complications such as recurrent cough, infection, and pulmonary atelectasis are potentially life-threatening. Diagnosis is made based on medical history and imaging, but in some cases, a computed tomography (CT) scan is required for confirmation before definitive treatment. The use of flexible bronchoscopy under local anesthesia is effective for extracting small foreign bodies, whereas large or sharp foreign bodies require bronchoscopy under general anesthesia. Case: A 65-year-old male presented with a three-week history of coughing up white sputum without coughing up blood, fever, or shortness of breath. A month earlier, the patient was hospitalized for decreased consciousness and status epilepticus for nine days, and diagnosed with anemia, hypokalemia, and hypoalbuminemia. The patient reported losing one tooth during the treatment. On examination, oxygen saturation was 98%, and chest examination results were normal. A chest X-ray showed a dental-density foreign body in the right bronchus, which was confirmed by CT. The patient underwent a foreign body extraction procedure from the right bronchus using flexible bronchoscopy with forceps and basket tips. Conclusion: Elderly patients with tracheobronchial foreign bodies often present with multiple comorbidities, a long disease course, and are sometimes asymptomatic. The use of flexible bronchoscopy is effective and safe in removing foreign bodies from the bronchi.